Optimization of Liquid Soap Containing Bentonite and Combination of Corn Oil and Virgin Coconut Oil For Cleansing Najs Mughalladzah - Chairunnisa Mahdi Pratama; Astri Desmayanti; Marchaban; Abdul Rohman (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2020)
This research was intended to formulate liquid bentonite soap using combination of corn oil andvirgin coconut oil used for cleansing najs mughalladzah (extreme najs). five formula of soap designated with I-Vapplying bentonite and combination of VCO and CO with different concentrations. The assessment of sopquality was based on organoleptic evaluation, foam stability, density, pH-value, and total of active component.Evaluation results were analyzed using simplex lattice design (SLD) to obtain optimum formula. Verificationof optimum formula was analyzed using one sample t-test with level of significance of 0.05. The resultsshowed that optimum concentration of bentonite was 6.5% with percentages of corn oil 85.43% and virgincoconut oil of 14.57%. Based on one sample t-test, there is no significant difference (pH > 0.05) from pH-valueresponse and foam stability between the predicted optimum formula as analyzed using SLD and actualformula. Bentonite liquid soap which is formulated using combination of corn oil and virgin coconut oilaccording to National Standardization Body SNI 2588:2017 so that the soap formula could be applied forcleansing najs mughalladzah.